IDENTIFICATION OF ANDESITE ROCK BASED ON THE RESISTIVITY VALUE IN SATUI AREA, SOUTH KALIMANTAN - Sri Cahyo Wahyono; Krisologus Genesa Atmadja; Simon Sadok Siregar (Jurnal Geofisika Eksplorasi, 2020)
Andesite rock identification has been carried out in Satui, South Kalimantan using the geoelectric method. Four lines resistivity measurement using Wenner configuration are used with a length of 200-350 m. The purpose of this study is to determine the depth, thickness and position of andesite rocks in the measurement area. Based on the results of processing there are three types of layers in the measurement area, clay with a resistivity of 9.760-68.373 Ωm, sandstones with a resistivity value of 68.373-324.509 Ωm and andesite with a resistivity ≥ 324.509 Ωm. The results of 2D interpretation show that the andesite rock in the entire first path are at a distance of 10.00-170.00 m, depth 6.76-9.94 m and thickness 7.36-10.54 m. Andesite in the second lane are found at a distance of 80-345 m, depth 1.25-9.94 m and thickness 2.62-10.54 m, on the third lane found at a distance of 100.00-200.00 m, depth 13.40 m and 3.90 m thick. Andesite in the fourth lane are found at a distance of 5.00-175.00 m with a depth of 6.76-13.40 m and thickness 1.95-10.54 m.